SEDIMENT TRANSPORT ANALYSIS FOR SECURING WATER (CASE STUDY: UPPER JENEBERANG RIVER) - M. Lukman; S. Pallu; F. Maricar; A. Thaha (International Conference on Coastal and Delta Areas, 2015)
The Jeneberang River Basin, upstream of Bili-Bili Dam Reservoir is divided into five (5) major sub-basins, named upper and middle main Jeneberang (Bili-Bili Dam Basin : 384.40 km2) , Salo Malino (85.89 km2), Salo Kausisi (37.50 km2), Jene Rakikang (42.2 km2) and Binanga Jajang (22.7 km2). Salo Malino is divided into more two (2) tributaries, named Salo Bulang (23.8km2) and Salo Ahuwa (37.1 km2). Bili-Bili dam is a multipurpose dam for irrigation, electricity, flood mitigation, and raw water. Bili-Bili Irrigation system covering 23,660 Ha of paddy field (Bissua system and Kampili system) of 270 bil.m3, Capacity for flood control 41 bil.m3, capacity for water supply 35 bil.m3, and the total storagevcapacity is 375 bill. M3, ofwhich the effective storage capacity is 346 bi.m3.Bili-Bili dam has been operated since 1999 year, serious sediment issues have been occurred in the Jeneberang river basin. Especially, after gigantic caldera collapse at March,2004, the sediment inflow volume in the reservoir have been reaches totally 49 million m3 as of May 2007. The objective of this study is to analyse the sediment transport at Upper Jeneberang river using HEC-RAS.. Which can be used to perform mobile bed computation. This study covering 32814.80 m length, consist of 80 reach (cross section). Large amount of sediment flowing to the dam could be reduce the capacity of the dam. Consequently the amount of water will reduced.The result is a continuous simulation of the change in cross section as sedimentation processes adjust to the hydraulic condition imposed by the water-sediment hydrograph and the base level control boundary conditions. Based on the analysis which show the erosion area and the sediment accumulated area, the decision maker can make the right choice to construct specific river structures at certain places to prevent sediment flowing to the dam for securing water.Keywords: Sedimentation, Sediment Transport, Securing Water